2018
DOI: 10.1007/s12035-018-1126-5
|View full text |Cite
|
Sign up to set email alerts
|

Early Downregulation of p75NTR by Genetic and Pharmacological Approaches Delays the Onset of Motor Deficits and Striatal Dysfunction in Huntington’s Disease Mice

Abstract: Deficits in striatal brain-derived neurotrophic factor (BDNF) delivery and/or BDNF/tropomyosin receptor kinase B (TrkB) signaling may contribute to neurotrophic support reduction and selective early degeneration of striatal medium spiny neurons in Huntington's disease (HD). Furthermore, we and others have demonstrated that TrkB/p75 imbalance in vitro increases the vulnerability of striatal neurons to excitotoxic insults and induces corticostriatal synaptic alterations. We have now expanded these studies by ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 101 publications
1
11
0
Order By: Relevance
“…One of the mechanisms contributing to synaptic impairment in the striatum of HD mouse models is the imbalance between BDNF receptors, TrkB and p75 NTR 42 , 43 . We found that RTP801 silencing increased TrkB levels in both homogenates and synaptosomes of R6/1 mice striatum in comparison to their shCtr-injected R6/1 littermates (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the mechanisms contributing to synaptic impairment in the striatum of HD mouse models is the imbalance between BDNF receptors, TrkB and p75 NTR 42 , 43 . We found that RTP801 silencing increased TrkB levels in both homogenates and synaptosomes of R6/1 mice striatum in comparison to their shCtr-injected R6/1 littermates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, specifically analyzing protein levels in synaptosomal preparations, we concluded that mhtt leads to a localized aberrant accumulation of RTP801 in synapses that could contribute to plasticity impairment in the pathology. In fact, structural alterations at the morphology and/or spine number in the striatum of the R6/1 55 and the KI 56 have been reported. This observation is also extended to other HD murine models such as N-terminal fragment R6/2 mice 57 , 58 and transgenic full-length htt YAC128 mice 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pharmacological treatment with fingolimod (FTY720) was performed as previously described [22]. FTY720 was obtained as a powder (Cayman Chemicals) and dissolved in EtOH 10% in distilled water (vehicle).…”
Section: Pharmacological Treatment In Vivomentioning
confidence: 99%
“…Striatal RTP801 silencing induced an increase of AMPA receptor subunit GluA1 at the homogenate fraction in shRTP801-injected R6/1 mice in comparison to shCtr-injected R6/1 mice whereas non-significant tendencies were observed at the synaptic compartment (Fig 7A). One of the mechanisms contributing to synaptic impairment in the striatum of HD mouse models is the imbalance between BDNF receptors, TrkB and p75 NTR 47,48 . We found that RTP801 silencing increased TrkB levels in both homogenates and synaptosomes of R6/1 mice striatum in comparison to their shCtr-injected R6/1 littermates (Figure 7B) whereas p75 NTR was nor modified in any compartment analyzed (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…However, specifically analyzing protein levels in synaptosomal preparations, we concluded that mhtt leads to a localized aberrant accumulation of RTP801 in synapses that could contribute to plasticity impairment in the pathology. In fact, structural alterations at the morphology and/or spine number in the striatum of the R6/1 59 and the KI 60 have been reported. This observation is also extended to other HD murine models such as N-terminal fragment R6/2 mice 6163 and transgenic full-length htt YAC128 mice 64 .…”
Section: Discussionmentioning
confidence: 99%